(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Service quality is an important aspect that has a direct impact on company. In addition, it is to be one of the consumer’s judgement in purchasing a product or service. Tight business competition and high consumers’ interest in training services encourage companies to enhance their service quality. The aims of this research are (1) to assess the service quality of coffee cupping training using weighted SERVPERF; (2) to analyze consumers’ response to the service quality provided by management; and (3) to analyze the effect of service quality on word of mouth in which customer satisfaction as a moderator variable. This research was conducted in Indonesian Coffee and Cocoa Research Institute. Survey method was applied to collect primary data by using questionnaire. Judgement sampling was used to select 102 respondents. The data were analyzed by descrip- tive method and statistical analysis. Moderator regression analysis was applied to predict the effect of service quality on word of mouth in which customer satis- faction as a moderating variable. The research found that the perceived service quality of coffee cupping training was 3.736 which categorized in relatively good on providing services. There were 3 attributes of service quality that must be immediately improved, among others (i) conformity of materials, visual practices and information provided by instructors to consumers’ needs; (ii) understand- able and up to date training materials; and (iii) duration of the training is matching with the consumers’ demand. The result of moderator regression analysis showed that interaction between service quality and customer satisfaction was not signifi- cant to word of mouth. Thus, customer satisfaction could not act to moderate in providing a better understanding of relationship between service quality and word of mouth than each variable on the model. There are expected external factors beyond the existing models that influences on word of mouth.